Passive solar space and water heating systems - Lo, S. N. G. (Cranfield University, 1990)
The performance of three types of passive solar feature has been studied; fifteen Roof-Space Collectors on an estate of low energy houses at the Milton Keynes Energy Park, 101m2 of Thermosyphoning Air Panels at a county primary school in Nazeing, Essex, and three Thermosyphon Solar Water Heaters installed on a group of three terraced cottages at Cranfield, Bedfordshire. Each of these passive solar features was monitored intensively for at least one heating season using dedicated data-acquisition systems. The maximum specific annual solar contributions to the auxiliary space/water heating systems were 128 kWh/M2 , 78 kWh/M2' and 104 kWh/M2 respectively. The corresponding payback periods were 25,37 & 21 years respectively, on replication.